Millets: The Miracle Grains - N. SWAMINAIDU; S.K.GHOSH; K. MALLIKARJUNA (International Journal of Pharma and Bio Sciences, 2015)
The origin of millet is diverse with varieties coming from both Africa and Asia. Millets are consumed as staple food, feed and drinks. Millets are nutritionally equivalent or superior to most cereals and contains high levels of methionine, cystine, and other vital amino acids for human health. These are rich in micronutrients, particularly iron, calcium, magnesium, phosphorous, zinc and potassium. Millets are often termed as nutria-cereals / nutraceuticals realizing their nutritional value. Millets are very hardy crop grown in very harsh climate, less water, poor or nutrient deficient soils without any fertilizer and pesticides. This can turn out to be a tremendous national gain especially in the ensuing decades of erratic climate, global warming and reduced water availability. Millets can become the crop of security as it can provide securities for food, fodder, health, nutrition, livelihood and ecology. In marginal areas millets are the best available alternative for farmers to get reliable harvest, food and nutrition. If the development issues that confound or influence the importance and status of millets as miracle grains are addressed, the farmers would surely promote the cultivation of millets.